2018
DOI: 10.1016/j.jcm.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided Dry Needling Treatment of Myofascial Trigger Points for Piriformis Syndrome Management: A Case Series

Abstract: For these 3 patients with piriformis syndrome who were treated with ultrasound-guided dry-needling treatment, their symptoms resolved and their quality of life improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
5
22
0
Order By: Relevance
“…This study showed that ultrasound‐guided DN is an effective therapeutic approach for pain management in PMS patients. This finding is consistent with a previous case series showing that sono‐guided DN had a good effect on the decrement of buttock pain intensity in PMS patients …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that ultrasound‐guided DN is an effective therapeutic approach for pain management in PMS patients. This finding is consistent with a previous case series showing that sono‐guided DN had a good effect on the decrement of buttock pain intensity in PMS patients …”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a previous case series showing that sono-guided DN had a good effect on the decrement of buttock pain intensity in PMS patients. 29 The mechanisms of action of DN in PMS patients are not well established. The effectiveness of DN is mostly based on other conditions, such as the presence of myofascial pain syndrome or trigger points.…”
Section: Pain Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been established as a reliable tool to diagnostically visualize myofascial trigger points, which may be seen in a piriformis muscle with increased resting tone . In addition, high‐resolution ultrasound has been used to diagnose nerve entrapment in the upper extremities, as nerve compression is correlated with increased nerve cross‐sectional area as seen on ultrasound .…”
Section: Diagnosismentioning
confidence: 99%
“…18 Ultrasound has been established as a reliable tool to diagnostically visualize myofascial trigger points, which may be seen in a piriformis muscle with increased resting tone. [47][48][49] In addition, high-resolution ultrasound has been used to diagnose nerve entrapment in the upper extremities, as nerve compression is correlated with increased nerve cross-sectional area as seen on ultrasound. 50 Ultrasound has been shown to be a reliable tool in the assessment of the sciatic nerve cross-sectional area in healthy controls, 51 but additional research is needed regarding the ultrasonographic assessment of the sciatic nerve in patients with suspected piriformis syndrome.…”
Section: Imagingmentioning
confidence: 99%